Optimizing Community Health Worker Knowledge for Hypertension Prevention in Older Adults - Nandita Putri; Wulan Tri Arfida; Juhanis Juhanis; Fikram Basri (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Hypertension is a major health issue among older adults and is often referred to as a silent killer due to its asymptomatic progression. Community health cadres play a key role in delivering basic health services, yet their knowledge of hypertension prevention is often limited. This community engagement program aimed to enhance cadre knowledge and skills through structured health education and physical activity interventions. The methods included lectures, interactive discussions, pre- and post-tests, and direct mentoring in senior exercise sessions implemented under the SABTUA (Saturday Activities with Older Adults) program. Pre-test results revealed that most cadres demonstrated very low knowledge levels (83.3%). After the intervention, post-test results showed significant improvement, with 66.6% in the good category and 33.3% in the excellent category. The SABTUA program also received positive responses from older adults, reflected in the increasing number of participants at each session. These findings demonstrate that a combination of health education and structured physical activity can improve both cadre awareness and older adults’ participation in hypertension prevention. Sustained support from local governance is essential to ensure the program’s long-term impact on improving the quality of life of older adults.